The Effect of Scrambled Picture Series on Students’ Ability In Writing Narrative Text at Grade X of SMA Negeri 1 Siantar - Damaris Nurtama Sihaloho; Partohap Saut Raja Sihombing; Melda Veby Ristella Munthe (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aimed to investigate the impact of Scrambled Pictures Stories media on students’ writing abilities in narrative texts among grade X students at SMA Negeri 1 Siantar. The theoretical framework was based on the work of Macon, Bewell, and Vogt. A quantitative research methodology was employed for this study. The population consisted of grade X students at SMA Negeri 1 Siantar for the academic year 2024/2025. The researcher selected two classes as samples: X-5 served as the experimental group, comprising 36 students, while X-6 acted as the control group, also with 36 students. The experimental group received instruction through Scrambled Pictures Stories media, whereas the control group was taught using conventional strategies. Data were collected via pre-tests and post-tests administered to both groups. The mean score for the experimental group in the pre-test was 58.55, compared to 48.97 for the control group. Conversely, the post-test mean score for the experimental group was 72, while the control group achieved a mean score of 53.69. The researcher utilized tests as the instrument for data collection. The t-test result was 329.33, exceeding the t-table value of 1.667 at a 5% significance level. This significant result indicates that the alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected, demonstrating a significant effect of using Scrambled Pictures Stories media on the narrative writing skills of grade X students at SMA Negeri 1 Siantar.